PENERAPAN PROFESIONALISME DAN INDEPENDENSI AUDITOR TERHADAP TINGKAT MATERIALITAS (Jurnal Riset Akuntansi, 2022)
The purpose of this study is to determine how professionalism and independence’s auditor affect the level of materiality at 9 Public Accounting Firms in Bandung. This study used descriptive and verification methods using multiple linear regression analysis. The results of this study show that auditor’s professionalism has a strong effect on the materiality level, while independence has a moderate effect on the materiality level. The conclusion is the higher professionalism and independence of an auditor, the better materiality determining considerations. Keywords : Auditor’s Professionalism, Independence, and Materiality Level.